Associations of oxidative balance score with hyperuricemia and gout among American adults: a population-based study - Wang, Kai; Wu, Jinyi; Deng, Minggang; Nie, Jiaqi; Tao, Fengxi; Li, Qingwen; Luo, Xin; Xia, Fang (Frontiers in Endocrinology, 2024)
The current study aimed to assess the relationships between OBS and OBS subclasses (dietary and lifestyle OBS) with risks of hyperuricemia (HUA) and gout among American adults. Participants in the National Health and Nutrition Examination Survey from 2007 to 2018 were initially recruited and then the final sample was restricted to adults without missing values about serum uric acid, gout, OBS and covariates. Rao-Scott adjusted chi-square test and analysis of variance were utilized to compare the baseline characteristics in adults of different quartiles of OBS, while the weighted stepped logistic regression models were used to explore the associations of overall, dietary and lifestyle OBS with the risks of HUA and gout. Weighted restricted cubic spline analyses were conducted to explore the nonlinear dose-response associations. Weighted quantile sum regression models were employed to assess the contributions of multiple components. The final sample consisted of 22,705 participants aged 20 years and older, which was representative of approximately 197.3 million noninstitutionalized American adults. HUA and gout prevalence decreased with OBS quartiles. Compared with adults in the first quartile of OBS, those in the second (OR: 0.85, 95%CI: 0.72-0.99), third (OR: 0.71, 95%CI: 0.58-0.85), and fourth (OR: 0.48, 95%CI: 0.38-0.61) quartiles of OBS had reduced risks of hyperuricemia. Similarly, adults in the second (OR: 0.70, 95%CI: 0.51-0.97) quartile of OBS was related to the lower gout risk in comparison to adults in the lowest quartile. Regarding OBS subclasses, dietary and lifestyle OBS were both negatively correlated with the risk of HUA, and only higher lifestyle OBS was significantly associated with lower gout risk. Furthermore, the subgroup analyses and interaction effects also substantiated similar effects. Significant nonlinear dose-response relationships were observed between overall, dietary and lifestyle OBS with HUA risk as well as that of lifestyle OBS with gout risk. This study strongly suggests the significant negative associations of OBS with HUA and gout in American adults, and provides a dietary and lifestyle guideline to reduce the risks.